PENGETAHUAN LOKAL MASYARAKAT ADAT BADUY DALAM PRANATA SOSIAL UNTUK MENUNJANG KETAHANAN PANGAN - Mirajiani, Mirajiani; Widi, Siti Widiati (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
The Baduy Indigenous Community's livelihood system, like society in general, of course interacts, socializes and produces a value system that applies in life based on a distinctive cultural system. The Baduy Indigenous Community implements local knowledge in social, economic, cultural and agricultural systems and logistics systems, in an effort to meet food needs. The method in this research is a descriptive method with a qualitative approach, which is carried out in the Baduy Indigenous Community. The Baduy community religiously believe in God, the belief of the Indigenous Baduy community is referred to as Sunda Wiwitan who believes in ancestral spirits (animism), in its development it is also influenced by Buddhism, Hinduism, and Islam. Local knowledge in the social institutions of the Indigenous Baduy Community can cover several aspects including: social aspects related to trust and leadership as well as community institutional systems, and economic aspects related to family livelihoods as an effort to fulfill food needs. Sociologically and anthropologically, the Baduy Indigenous people's paddy fields do not change the contours of the land, so as not to damage the surrounding environment used in agricultural activities, intercropping between vegetables and tubers, to maximize agricultural yields. The Baduy Indigenous People have a logistics system that is integrated with the rules of customs and traditions, to ensure the availability and authenticity of local commodities as staple food, with decent, equitable and affordable quality and sustainable to be used by the Baduy Indigenous Peoples, in supporting the fulfillment of food needs. In fulfilling other food security, it is obtained from the use of forest resources, plantations, livestock and selling accessories typical of Baduy, as well as woven fabrics to visitors, or traveling to sell, and being a tour guide for tourists visiting Baduy. Social institutions based on local knowledge, make the Baduy Indigenous People able to meet their basic needs for natural resources and existing human resources, and are carried out independently without depending on other parties, in fulfillment of food needs.